Characterization of Phototransduction Gene Knockouts Revealed Important Signaling Networks in the Light-Induced Retinal Degeneration. (26th February 2008) - Krishnan, Jayalakshmi; Lee, Gwang; Han, Sang-Uk; Choi, Sangdun
Abstract : Understanding the molecular pathways mediating neuronal function in retinas can be greatly facilitated by the identification of genes regulated in the retinas of different mutants under various light conditions. We attempted to conduct a gene chip analysis study on the genes regulated during rhodopsin kinase (Rhok - / - ) and arrestin (Sag - / - ) knockout and double knockouts in mice retina. Hence, mice were exposed to constant illumination of 450 lux or 6, 000 lux on dilated pupils for indicated periods. The retinas were removed after the exposure and processed for microarray analysis. Double knockout was associated with immense changes in gene expression regulating a number of apoptosis inducing transcription factors. Subsequently, network analysis revealed that during early exposure the transcription factors, p53, c-MYC, c-FOS, JUN, and, in late phase, NF - B, appeared to be essential for the initiation of light-induced retinal rod loss, and some other classical pro- and antipoptotic genes appeared to be significantly important as well.